Eco‐Friendly Methodology for the Formation of Aromatic Carbon–Heteroatom Bonds by Using Green Ionic Liquids. Issue 2 (26th November 2020) - Richards, Kenza; Petit, Eddy; Legrand, Yves‐Marie; Grison, Claude
Abstract: A new sustainable method is reported for the formation of aromatic carbon–heteroatom bonds under solvent‐free and mild conditions (no co‐oxidant, no strong acid and no toxic reagents) by using a new type of green ionic liquid. The bromination of methoxy arenes was chosen as a model reaction. The reaction methodology is based on only using natural sodium bromine, which is transformed into an electrophilic brominating reagent within an ionic liquid, easily prepared from the melted salt FeCl3 hexahydrate. Bromination reactions with this in‐situ‐generated reagent gave good yields and excellent regioselectivity under simple and environmentally friendly conditions. To understand the unusual bromine polarity reversal of sodium bromine without any strong oxidant, the molecular structure of the reaction medium was characterised by Raman and direct infusion electrospray ionisation mass spectroscopy (ESI‐MS). An extensive computational investigation using density functional theory methods was performed to describe a mechanism that suggests indirect oxidation of Br − through new iron adducts. The versatility of the methodology was successively applied to nitration and thiocyanation of methoxy arenes using KNO3 and KSCN in melted hexahydrated FeCl3 . Abstract : Polarity reversal : A new methodology for C‐heteroatom bond formation is described. The reaction is performed in a green ionic liquid easily prepared from melted FeCl3 ⋅6 H2 O and natural salts NaBr, KSCN or KNO3, under unprecedented conditions of sustainability. DFT calculations revealed the formation of a Fe‐anionic species inducing the challenging transformation of the anionic substituent into an electrophilic reagent.